Co-creation and smart cities : looking beyond technology - Graaf, Shenja Van Der, 1976-; Long, Le Anh Nguyen; Veeckman, Carina (Emerald points., 2021)
Cities are possibly the most dynamic and important administrative units today. Cities play big roles in addressing many of the complex challenges the world is facing today, including climate change, public health, and migration. This places pressure on public administration and the public sector, to do more with less, particularly at the local level where government services have the most direct impact on people's everyday lives as well as paradigmatic societal shifts associated with the rise of platform economies and new consumption patterns which transform public service delivery whilst changing public expectations. Co-creation and Smart Cities: Looking Beyond Technology highlights ways to meet these new demands with a more robust value-based perspective on public service development and delivery, specifically via co-creation. Co-creation is a way to plan, execute and evaluate public service design and delivery for contemporary cities, a valid means to support the 'balancing act' of promoting efficient and cost-effective governance. Built on insights gained through years of experience with and research on co-creation, as well as testimonials from practitioners, this volume presents collaborative and innovative solutions associated with smart city ideals, while continuing to develop a citizen-centric focus that is sustainable over time. Co-creation and Smart Cities helps structure co-creation processes that foster responsible innovation and a systemic, value-based approach to sustainable urban development. This title will be of interest to government officials, researchers and bottom-up communities looking to implement methods for co-creation within cities.